A atuação da Organização dos Estados Americanos (OEA) para a proteção da democracia nos países da América Latina: uma análise dos casos da Venezuela (2002), Haiti (2004), Honduras (2009) e Equador (2010) - Zanoti, Dante Gabriel Nunes (2021)
This essay aims to analyze the performance of the Organization of American States (OAS) in the face of episodes of change in the democratic order in Latin American countries. For this, we seek to review the existing bibliography in the field of International Relations on norms and institutions and their role in the promotion and defense of democracy. Next, the norms and mechanisms for protecting democracy created by the OAS are presented, with an emphasis on the Inter-American Democratic Charter (CDI), approved in 2001. The behavior of the OAS in specific cases of democratic crises is then analyzed since 2001, namely, Venezuela (2002), Haiti (2004), Honduras (2009) and Ecuador (2010) and then a comparative analysis between the cases is made. It is concluded that the performance of the OAS in each crisis varied according to some elements that concern both the domestic policy of the country in crisis and the insertion of this country in the regional and global scope, the interests of the foreign policy of the United States and the concomitant agency of other international organizations.